Endophyte-inoculated rhizomes of Paris polyphylla improve polyphyllin biosynthesis and yield: a transcriptomic analysis of the underlying mechanism - Zhang, Qing; Chang, Sheng; Yang, Ying; Xi, Congfang; Dong, Yumei; Liu, Lufeng; He, Yunchao; Liu, Yu; Cai, Bo; Liu, Tao (Frontiers in Microbiology, 2023)
Polyphyllin from Paris polyphylla var. yunnanensis exhibits anti-inflammatory, analgesic, antibacterial, and antiviral properties. However, the current production of polyphyllin can barely meet market demand. To improve the content of polyphyllin produced by P. polyphylla, two endophyte strains, Bacillus cereus LgD2 and Fusarium oxysporum TPB, were isolated from Paris fargesii Franch. and inoculated in the roots of P. polyphylla. Both symbiotic strains significantly promoted the accumulation of saponins in P. polyphylla. To reveal the mechanism underlying the promotion of polyphyllin biosynthesis by LgD2 and TPB, rhizomes of P. polyphylla treated with the two strains were collected for transcriptome sequencing. RNA-seq and qRT-PCR analyses showed that endophytic inoculation did not promote polyphyllin accumulation by enhancing the upstream terpene biosynthesis pathway, but probably by up-regulating the downstream cytochrome P450 (CYP450) and UDP-glycosyltransferase (UGT) genes associated with polyphyllin biosynthesis. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses of differentially expressed genes indicated that inoculation with LgD2 and TPB played a positive role in promoting the defense against pathogenic bacteria, enhancing the biosynthesis of carbohydrates, attenuating the process of nitrogen metabolism, and maintaining the equilibrium of the redox reaction homeostasis, potentially indirectly enhancing the polyphyllin yield of P. polyphylla. By combining differentially expressed genes screening, weighted correlation network analysis, and phylogenetic tree analyses, 17 CYP450 and 2 UGT candidate genes involved in the biosynthesis of polyphyllin I, polyphyllin Ⅱ, polyphyllin Ⅶ, polyphyllin D, and polyphyllin H were identified. These results suggest that endophytes probably effectively promote the accumulation of polyphyllin by regulating key downstream genes in biosynthetic pathways. This study provides a new approach for investigating the regulatory mechanisms of endophytes that promote the production and accumulation of polyphyllin in P. polyphylla, providing a basis for further elucidating the mechanisms of plant-endophyte interactions.